EFFECT OF TEMPERATURE AND LIGHT ON THE PHOTOSYNTHESIS AS MEASURED BY CHLOROPHYLL FLUORESCENCE OF CULTURED Kappaphycus sp. (SAKOL STRAIN) FROM INDONESIA - Lidemen Lidemen; Asda Laining; George N Nishihara; Ryuta Terada (Indonesian Aquaculture Journal, 2013)
Photosynthetic performance of carrageenophyte (Solieriaceae; Rhodophyta) cultured in Indonesia, Kappaphycus sp. (Sakol strain), was investigated at various temperature and light conditions related to their cultivation performance. A “pulse-amplitude modulatedchlorophyll fluorometer” (Diving-PAM) was used to generate a rapid light curves (RLCs) to provide estimates relative electron transport rates (rETR) for over 10 temperatures (i.e., 16oC to 34oC) and at nine photosynthetic active radiation (PAR) levels, which ranged from 0 to 1,000 mol photons m-2 s-1. The initial slope (α), photo-inhibition coefficient (β), and the coefficient of maximum photosynthesis assuming no photo-inhibition (γ) is calculated by fitting the RLCs on a nonlinear model by using a two-level hierarchical Bayesian model. The experimental results showed that Kappaphycus sp. required temperatures ranging from 26oC to 34oC to maintain their high levels of photosynthetic activity. Saturating irradiace (Ek) at the temperature range occured ranging from 120 to 150 μmol photons m-2 s-1. The model equation that have been derived from this series experiment can be used to determine the requirement of temperature and light intensity (irradiance) of any seaweed species.